The battle of methods In the education of the deaf - Rathna N (Journal of All India Institute of Speech and Hearing, 1970)
The education of the deaf has been among the earliest of the special educational problems to receive organized attention.   Aristotle gave some thought to it and felt that the deaf could neither speak nor understand others' speech and that they were incapable of instruction (Silverman and Davis 1966). Cardano in the  16th Century established that the deaf could be taught to comprehend written symbols.   That they could be taught speech was shown by the Spanish Ponce de Leon (1555).   His compatriot Bonet in 1620 wrote a manual of speech teaching for the deaf.    However,  our recent traditions started from the  18th century with Abbe de l'Epee in France who advocated the use of the sign language and Heinicke about the same time in Germany who advocated oralism, that is, speech and speech reading.   The first school in Scotland was started in 1760 and the one in England proper was started in 1792.